Expression analysis of cinnamoyl-CoA reductase (CCR) gene in developing seedlings of Leucaena leucocephala: A pulp yielding tree species - Srivastava, Sameer; Gupta, Ranadheer K.; Arha, Manish; Vishwakarma, Rishi K.; Rawal, Shuban K.; Kishor, P. B. Kavi; Khan, Bashir Mohammad (Plant Physiology and Biochemistry, 2011)
Removal of lignin is a major hurdle for obtaining good quality pulp. Leucaena leucocephala (subabul) is extensively used in paper industry in India; therefore, as a first step to generate transgenic plants with low lignin content, cDNA and genomic clones of CCR gene were isolated and characterized. The cDNA encoding CCR (EC 1.2.1.44) was designated as LI-CCR; the sequence analysis revealed an Open Reading Frame (ORF) of 1005 bp. Phylogenetic analysis showed that LI-CCR sequence is highly homologous to CCRs from other dicot plants. The 2992 bp genomic clone of Leucaena CCR consists of 5 exons and 4 introns. The haploid genome of L leucocephala contains two copies as revealed by DNA blot hybridization. LI-CCR gene was over-expressed in Escherichia coli, which showed a molecular mass of approximately 38 kDa. Protein blot analysis revealed that LI-CCR protein is expressed at higher levels in root and in stem, but undetectable in leaf tissues. Expression of CCR gene in Leucaena increased up to 15 d in case of roots and stem as revealed by QRT-PcR studies in 0-15 d old seedlings. ELISA based studies of extractable CCR protein corroborated with QRT-PCR data. CCR protein was immuno-cytolocalized around xylem tissue. Lignin estimation and expression studies of 5,10 and 15 d old stem and root suggest that CCR expression correlates with quantity of lignin produced, which makes it a good target for antisense down regulation for producing designer species for paper industry. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: Cinnamoyl-CoA reductase; Developing seedling; Leucaena leucocephala; Lignin biosynthesis

Efficient shoots regeneration and genetic transformation of bacopa monniera - Kumari, Uma; Vishwakarma, Rishi K.; Gupta, Neha; Ruby; Shirgurkar, M. V.; Khan, Bashir Mohammad (Physiology and Molecular Biology of Plants, 2015)
Bacopa monniera is an important source of metabolites with pharmaceutical value. It has been regarded as a valuable medicinal plant and its entire commercial requirement is met from wild natural population. Recently, metabolic engineering has emerged as an important solution for sustained supply of assured and quality raw material for the production of active principles. Present report describes efficient in vitro multiplication and transformation method for geneticmanipulation of this species. MS medium supplemented with 2 mgl(-1) BA and 0.2 mgl(-1) IAA was found optimum for maximum shoot regeneration (98.33 %) from in vitro leaves with 2-3 longitudinal cuts. Agrobacterium tumefaciens-mediated transformation method was used for generating transgenic B. monniera plants. Putative transformants were confirmed by GUS assay and PCR based confirmation of hptII gene. DNA blot analysis showed single copy insertion of transgene cassette. An average of 87.5 % of the regenerated shoots were found PCR positive for hptII gene and GUS activity was detected in leaves of transgenic shoots at a frequency of 82.5 % The efficient multiple shoots regeneration system described herein may help in mass production of B. monniera plant. Also, the high frequency transformation protocol described here can be used for genetic engineering of B. monniera for enhancement of its pharmaceutically important metabolites.

Enhanced activity of Withania somnifera family-1 glycosyltransferase (UGT73A16) via mutagenesis - Singh, Somesh; Patel, Krunal A.; Sonawane, Prashant D.; Vishwakarma, Rishi K.; Khan, Bashir M. (World Journal Of Microbiology & Biotechnology, 2018)
This work used an approach of enzyme engineering towards the improved production of baicalin as well as alteration of acceptor and donor substrate preferences in UGT73A16. The 3D model of Withania somnifera family-1 glycosyltransferase (UGT73A16) was constructed based on the known crystal structures of plant UGTs. Structural and functional properties of UGT73A16 were investigated using docking and mutagenesis. The docking studies were performed to understand the key residues involved in substrate recognition. In the molecular model of UGT73A16, substrates binding pockets are located between N- and C-terminal domains. Modeled UGT73A16 was docked with UDP-glucose, UDP-glucuronic acid (UDPGA), kaempferol, isorhamnetin, 3-hydroxy flavones, naringenin, genistein and baicalein. The protein-ligand interactions showed that His 16, Asp 246, Lys 255, Ala 337, Gln 339, Val 340, Asn 358 and Glu 362 amino acid residues may be important for catalytic activity. The kinetic parameters indicated that mutants A337C and Q339A exhibited 2-3 fold and 6-7 fold more catalytic efficiency, respectively than wild type, and shifted the sugar donor specificity from UDP-glucose to UDPGA. The mutant Q379H displayed large loss of activity with UDP-glucose and UDPGA strongly suggested that last amino acid residue of PSPG box is important for glucuronosylation and glucosylation and highly specific to sugar binding sites. The information obtained from docking and mutational studies could be beneficial in future to engineer this biocatalyst for development of better ones.